ESTIMATION OF GENETIC DIVERSITY IN SILVER CATFISH (Chrysicthys nigrodigitatus) USING RANDOM AMPLIFIED POLYMORPHIC DNA (FUDMA JOURNAL OF SCIENCES, 2024)
The Silver catfish (Chrysicthys nigrodigitatus) is widely distributed along River Niger.This study was carried out to characterize Silver Catfish found along River Niger, with the help of morphometric and random amplified polymorphic DNA for genetic analysis to determine variation in strain that can be used for identification of the strains and possible allocation. Samples were collected from three stations, namely; Illushi, Illah and Onitsha and total of 1 50 samples (50 each) of silver catfish was collected from landing station. Where 12% of the total sampled fish was used for genetic analysis and 100% of the sample was used for morphometric analysis. Result obtain from the morphometric analysis along River Niger show that dorsal fin length and head length with a value of 0.749 and 0.230 respectively are significantly different (p
Keywords: Silver catfish; morphometric; amplified; polymorphic; variation